Pengaruh Formulasi Nugget Udang Jerbung (Penaeus Merguiensis) dengan Subtitusi Puree Ubi Cilembu dan Ampas Kelapa Terhadap Mutu Kimia dan Organoleptik - Hardiyanti, Gladies Ayu; Sucahyo, Bambang Sigit; Prayudanti, Adhania Andika (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to determine the substitution concentration of Cilembu sweet potato purÃ©e and coconut pulp that provides the best chemical and organoleptic quality for white shrimp nuggets. The research method used is a laboratory experiment. Parametric data, including carbohydrate content, protein content, fat content, and fiber content, were analyzed for normality and homogeneity, followed by analysis of variance (ANOVA) using SPSS software. White shrimp nuggets are a restructured meat product that falls into the category of frozen ready-to-eat foods. The identified conclusion is that different concentrations of Cilembu sweet potato purÃ©e and coconut pulp do not significantly affect carbohydrate content, fat content, fiber content, and protein content. However, they do influence the texture and taste of white shrimp nuggets, but not their aroma and color. Based on effectiveness testing, the best treatment was identified as P4.